GREEN MARKETING STRATEGIES AND CONSUMER PURCHASE BEHAVIOR TOWARD SUSTAINABLE PRODUCTS - Basyirah Basyirah; Reni Yesi. S; M. Joni; Ansir Launtu; Klemens Mere (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study examines the influence of green marketing strategies on consumer purchase behavior toward sustainable products through a systematic literature review approach. The increasing global concern over environmental degradation and climate change has encouraged businesses to adopt environmentally responsible marketing practices. However, the effectiveness of these strategies in influencing actual consumer behavior remains a subject of ongoing debate. This study aims to synthesize existing research findings to identify the key factors that determine consumers’ willingness to purchase sustainable products. The research method employed in this study is a systematic literature review, following the framework proposed by John W. Creswell (2014) and further refined by Hannah Snyder (2019). Data were collected from reputable academic databases such as Google Scholar, Scopus, and Web of Science, focusing on publications from 2010 to 2024. A total of 30 relevant studies were selected based on predefined inclusion criteria, including relevance, academic rigor, and contribution to the field of green marketing and consumer behavior. The findings reveal that green marketing strategies significantly influence consumer attitudes; however, their impact on actual purchase behavior is mediated by several key factors. Environmental awareness, perceived value, trust, and social influence are identified as the primary determinants of consumer decisions. Among these, perceived value and trust play the most critical roles, while price sensitivity remains a major barrier to the adoption of sustainable products. Additionally, the study confirms the existence of an attitude–behavior gap, where consumers express positive environmental attitudes but do not consistently translate them into purchasing actions. The study concludes that effective green marketing strategies must go beyond raising awareness and should focus on enhancing product value, ensuring transparency, and building consumer trust. The findings provide important implications for businesses in designing more effective marketing strategies and for policymakers in promoting sustainable consumption. Future research is recommended to conduct empirical studies and explore the role of digital technologies in shaping green consumer behavior.